Dark energy as a kinematic effect - Jennen, H. [UNESP]; Pereira, J. G. [UNESP] (Elsevier, 2016)
We present a generalization of teleparallel gravity that is consistent with local spacetime kinematics regulated by the de Sitter group SO(1, 4). The mathematical structure of teleparallel gravity is shown to be given by a nonlinear Riemann-Cartan geometry without curvature, which inspires us to build the generalization on top of a de Sitter-Cartan geometry with a cosmological function. The cosmological function is given its own dynamics and naturally emerges nonminimally coupled to the gravitational field in a manner akin to teleparallel dark energy models or scalar-tensor theories in general relativity. New in the theory here presented, the cosmological function gives rise to a kinematic contribution in the deviation equation for the world lines of adjacent free-falling particles. While having its own dynamics, dark energy manifests itself in the local kinematics of spacetime.
Keywords: Cosmological function; Dark energy; de Sitter kinematics; Teleparallel gravity